Endemism in the Italian stonefly-fauna (Plecoptera) - Fochetti, Romolo (Zootaxa, 2020)
Remarks on the endemicity of the Italian stonefly-fauna are presented. Notes on conservation issues are also given, together with the updated list of stoneflies of Italy.